Integrasi Etika dan Regulasi dalam Penanganan Misinformasi di Media Digital pada Era Post-Truth - Delima, Wirda; Sazali, Hasan (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2025)
The post-truth era is marked by the prevalence of inaccurate information and the rapid spread of disinformation through digital media. This research explores the relationship between communication ethics and policy regulations as tools to address these challenges, focusing on regulations implemented to tackle disinformation. One example of the regulations analyzed is the General Data Protection Regulation (GDPR) in the European Union and Digital Media Regulations in Indonesia, which aim to limit the spread of false information while maintaining freedom of speech. The study also assesses the impact on individual privacy and freedom of expression. Furthermore, the role of stakeholders, including journalists, social media platforms, and users, in disseminating accurate and trustworthy information is analyzed. Using a qualitative approach, this study identifies the challenges in implementing these regulations and offers effective mitigation strategies. The findings suggest that collaboration between ethics, regulation, and digital literacy is key to building a healthier information ecosystem in the post-truth era. The practical implication of this research is that policymakers can design better regulations by considering digital media education, while social media platforms can implement policies that are more responsive to disinformation. It is hoped that the results of this research will provide valuable insights for policymakers, academics, and practitioners in designing more effective solutions to address disinformation.